Work, health and Covid-19: A literature review - Damini Purkayastha; Christophe Vanroelen; Tuba Bircan; Marthe Andrea Vantyghem; Clara Gantelet Adsera (European Trade Union Institute (ETUI), 2021)
With work a key vector of Covid-19 transmission, this report examines why it is critical that occupational health and safety measures take centre stage in mitigation policies. Workers in sectors declared essential by state authorities have been mandated to continue working in physical settings during the pandemic. Several such sectors involve many face-to-face contacts with colleagues and clients, meaning that workers face a higher risk of exposure to Covid-19. Unregulated safety measures, a lack of personal protective equipment and crowded settings further increase the risk in these sectors. Persisting inequalities are exacerbated by the pandemic, as low-wage workers, workers from ethnic minorities, migrant workers and women are overrepresented in these sectors. They also face intersecting factors, including precarious contracts, job insecurity, inadequate paid sick leave, a lack of bargaining power and low socioeconomic status. The risks faced by (recent) migrants are compounded by the fact that their residence permits, access to healthcare and housing may be mediated by their employers. Studies show that there is also a gender dimension to the OSH implications of the pandemic, with women facing a higher exposure to the disease, a higher care burden and an increased risk of domestic violence. These patterns of inequality play a significant role in a health crisis, determining who is at greater risk of becoming infected, and whether or not they will have access to healthcare and self-isolation. Besides recognising Covid-19 as an occupational disease and providing adequate protection to workers across sectors, it is important for OSH measures to go beyond workplace exposure to the disease and to include the various factors increasing exposure because of work. Policy recommendations include better representation of workers at all levels of employment, sector-specific OSH measures, broader EU-wide policies and infrastructures, improved job security and sick leave policies, disaggregated data collection and inclusive messaging.
Keywords: 330; coronavirus; health risk; Workplace; infection control; occupational health and safety; Corporate Health Management; Coronavirus; Gesundheitsrisiko; Arbeitsplatz; Infektionsschutz; Arbeitsschutz; Betriebliches Gesundheitsmanagement